Endoparasitises of the red fox (Vulpes vulpes) in the North of the Kharkiv district - Mazannyі, O.; Liulin, P.; Nikiforova, O. (Scientific Progress & Innovations, 2023)
During the martial law, the fox populations was increased, which are not only a source of the rabies virus, but also carriers of parasitic diseases pathogens. The aim of the research was to study the helminth fauna of wild foxes to establish their role in the distribution of helminthoses among wild and domestic stray carnivores. In February 2022, 5 carcasses of red foxes (3 males and 2 females) aged 2.5–5.5 years old from Dergachyvska city united territorial community were examined by the method of complete helminthological autopsy and by standardized flotation and sedimentation coproscopic methods. According to the results of the autopsy, the extensiveness (EI) of heartworm and toxascarosis infestations was 40 % each. Dirofilaria immitis was detected only in female foxes (EI=100 %). The length of female dirofilaria exceeded the length of male by 9.5 cm and was on average 32.0±0.5 cm. Two out of three males were infested with toxascaris (EI=66.7 %). In the older male (5,5 years old) the number of toxascaris was 54.1 % less, but they were longer: males by 7.4 %, and females by 3.1 %. During the helmintoovoscopic examination of fecal samples using the flotation method, the extent of toxascarosis infestation was 40%, hookworm infestation – 60 %, trichuratosis infestation – 80 %, and isosporinosis infestation – 40 %. The intensity of egg production of Toxascaris was higher in the younger male fox: 25.67±0.67 eggs in 1 gram of feces, against 3.67±0.33, which is associated with a greater, almost twice, number of females detected by autopsy results nematodes (41 against 21 numbers). According to the standardized method of sedimentation, the extent of alarial invasion was 80 % with a mostly low degree of invasion intensity. So, research using three methods: helminthological autopsy, examination of feces for the presence of helminth eggs or protozoan oocysts (flotation and sedimentation methods) made it possible to determine the composition of the endoparasitofauna of foxes. In red foxes, the causative agents of six invasive diseases were detected. All animals had a mixed invasion: in males ‒ three and five-component diseases, in particular, dirofilariosis-alariosis-isosporinosis, toxascarosis-ancylostomidosis-trichuratosis and toxascarosis-ancylostomidosis-trichuratosis-alarosis-isosporinosis, and in both females foxes ‒ three component invasions of the same composition: dirofilariosis-trichuratosis-alariosis.